Plan Publicitario para la empresa MARTINIZIN dedicada a la venta de vehículos usados, provincia de Cotopaxi. - Fernández Pacheco, María Augusta (2021)
The present investigation is a work that is directed to the Martinizin company, it intends to strengthen and implement advertising strategies to improve the image and sales of said entity; The main objective of the research was to develop an Advertising Plan for the company in order to improve its sales income and its low market share. The research has a qualitative approach of a descriptive type, of an exploratory nature and bibliographic-documentary reference and the application of an interview that seeks to integrate the people involved, both internal and external. The results indicate the need for the company to integrate into the competitive environment through different means of communication with the application of creative strategies to optimize the sale of used vehicles. The conclusions express the resulting effectiveness for the company and the responsibility to respond for the quality of its service offered, only with the application of advertising promotion alternatives, which support the operational development in internal management, related to sales, improving its image. and its share of the used vehicle market.